2021
DOI: 10.1101/2021.11.10.468102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time Image Denoising of Mixed Poisson-Gaussian Noise in Fluorescence Microscopy Images using ImageJ

Abstract: Fluorescence microscopy imaging speed is fundamentally limited by the measurement signal-to-noise ratio (SNR). To improve image SNR for a given image acquisition rate, computational denoising techniques can be used to suppress noise. However, analytical techniques to estimate a denoised image from a single frame are either computationally expensive or rely on simple noise statistical models. These models assume Poisson or Gaussian noise statistics, which are not appropriate for many fluorescence microscopy app… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Besides, our demonstrated model can work with other super-resolution target generation methods like STED/STORM/PALM/SIM. While we evaluated the technique on super-resolution fluorescence microscopy, this approach shows promise for extension to other deep learning based image enhancements (e.g., image denoising networks [10, 43], image super-resolution [26, 44, 45, 46, 47], image segmentation networks [28], and other imaging modalities like X-ray [48, 49, 50] and MRI imaging [51]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, our demonstrated model can work with other super-resolution target generation methods like STED/STORM/PALM/SIM. While we evaluated the technique on super-resolution fluorescence microscopy, this approach shows promise for extension to other deep learning based image enhancements (e.g., image denoising networks [10, 43], image super-resolution [26, 44, 45, 46, 47], image segmentation networks [28], and other imaging modalities like X-ray [48, 49, 50] and MRI imaging [51]).…”
Section: Discussionmentioning
confidence: 99%
“…FCNs [62] are used for pixel-wise prediction, e.g. semantic segmentation [39], image denoising [10], super-resolution [37] and low dose computer tomography X-ray reconstruction [63]. Fig.…”
Section: Fcns With Dense Encoder Decodermentioning
confidence: 99%
See 2 more Smart Citations
“…, exhibited the usage of a specialized software on tissue and tumor images thereby imparting a stable basis for the continuing improvement of tissue imaging software. Fluorescence microscopy imaging pace is essentially restricted through the dimension signal-to-noise ratio (SNR), Mannam et al, (2022). Furthermore, their study revealed that in order to enhance picture SNR for a given picture acquisition rate, computational denoising strategies may be used to suppress noise.…”
Section: Related Workmentioning
confidence: 99%